The Effects of Biostimulants on Induced Plant Defense - Pereira, Ramom Vasconcelos; Filgueiras, Camila C.; Dória, Joyce; Peñaflor, Maria Fernanda G. V.; Willett, Denis S. (Frontiers in Agronomy, 2021)
The search for innovative and alternative methods for chemical control to manage pests is an increasingly growing reality. The use of biostimulants such as plant growth promoting rhizobacteria (PGPR) and humic acids (HA) has been shown to improve many agronomic characteristics of plants while increasing yield. These biostimulants also alter the production of secondary metabolites with consequences for insect herbivores. Here we review the role of biostimulants such as PGPR and HA in promoting and eliciting plant defenses. The cascading effects of using these biostimulants on insect herbivores and their natural enemies are discussed in this context. Synergism between biostimulants are also discussed. The potential role of these products in augmenting agricultural productivity is highlighted as is further need for additional research. This review highlights the potential of this tool to enhance integrated pest management in agricultural production systems, reduce the use of pesticides, and increase the efficiency of fertilization while supporting healthier more pest-resistant plants.